From inflation to recent cosmic acceleration: The fermionic Elko field driving the evolution of the universe - Pereira, S. H. [UNESP]; Guimarães, T. M. [UNESP] (IOP Publishing, 2017)
In this paper we construct the complete evolution of the universe driven by the mass dimension one dark spinor called Elko, starting with inflation, passing by the matter dominated era and finishing with the recent accelerated expansion. The dynamic of the fermionic Elko field with a symmetry breaking type potential can reproduce all phases of the universe in a natural and elegant way. The dynamical equations in general case and slow roll conditions in the limit H mpl are also presented for the Elko system. Numerical analysis for the number of e-foldings during inflation, energy density after inflation and for present time and also the actual size of the universe are in good agreement with the standard model of cosmology. An interpretation of the inflationary phase as a result of Pauli exclusion principle is also possible if the Elko field is treated as an average value of its quantum analogue.
Keywords: alternatives to ination; cosmology of theories beyond the SM; dark matter theory